Tumor Associated Neutrophils. Their Role in Tumorigenesis, Metastasis, Prognosis and Therapy - Masucci, Maria Teresa; Minopoli, Michele; Carriero, Maria Vincenza (Frontiers in oncology, 2019)
Tumor Associated Neutrophils (TANs) are engaged into the tumor microenvironment by cytokines and chemokines, can be distinguished according to their activation and cytokine status and effects on tumor cell growing in N1 and N2 TANs. N1 TANs exert an antitumor activity, by direct or indirect cytotoxicity. N2 TANs stimulate immunosuppression, tumor growth, angiogenesis and metastasis by DNA instability, or by cytokines and chemokines release. In tumor patients, either a high number of TANs and Neutrophil-to-Lymphocyte Ratio (NLR) do correlate with poor prognosis, and, so far, TAN counts and NLR can be regarded as biomarkers. Owing to the pivotal role of TANs in stimulating tumor progression, therapeutic strategies to target TANs have been suggested, and two major approaches have been proposed: (a) targeting the CXCL-8/CXCR-1/CXCR-2 axis, thereby blocking TANs or (b) targeting substances produced by polymorpho-nuclear cells that promote tumor growth. Many studies have been accomplished either and in animal models, whereas clinical studies are restrained, presently, due to the risk of inducing immunosuppression. In this review, we deeply discuss the anti-tumorigenic or pro-tumorigenic activity of TANs. In particular, TANs relevance in tumor prognosis and therapeutic strategies are widely described. On-going clinical trials, aimed to inhibit neutrophil recruitment into the tumor are also accurately debated.